Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1097/mlr.0000000000001879
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Cervical and Colorectal Cancer Screenings During the Pandemic in Community Health Centers

Abstract: Background: The coronavirus disease 2019 pandemic led to clinical practice changes, which affected cancer preventive care delivery. Objectives: To investigate the impact of the coronavirus disease 2019 pandemic on the delivery of colorectal cancer (CRC) and cervical cancer (CVC) screenings. Research Design: Parallel mixed methods design using electronic health record data (extracted between January 2019 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…4,5 CHCs can play an important role in preventive care and cancer control. [6][7][8][9][10][11] In a nationally representative study, for example, among people living within 20 miles of a CHC, patients were more likely to receive breast cancer screening than individuals receiving care elsewhere, particularly among people without health insurance. 7 Similar to many other cancer types, cervical cancer mortality rates in the United States have generally been higher in rural and nonmetropolitan areas than urban and metropolitan areas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 CHCs can play an important role in preventive care and cancer control. [6][7][8][9][10][11] In a nationally representative study, for example, among people living within 20 miles of a CHC, patients were more likely to receive breast cancer screening than individuals receiving care elsewhere, particularly among people without health insurance. 7 Similar to many other cancer types, cervical cancer mortality rates in the United States have generally been higher in rural and nonmetropolitan areas than urban and metropolitan areas.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found an overall decline in the receipt of cancer screening among CHC patients in the first year of the pandemic but did not report the trends for rural and urban CHCs. [8][9][10] This study aims to quantify rural-urban differences in up-to-date cervical cancer screening in CHCs before and during the pandemic and identify major contributing factors to these differences.…”
Section: Introductionmentioning
confidence: 99%